Infraposition of anterior maxillary implant‐supported single‐tooth restorations in adolescent and adult patients—A prospective follow‐up study up to 6 years. (5th August 2019) - Nilsson, Andrée; Johansson, Lars‐åke; Stenport, Victoria F.; Wennerberg, Ann; Ekfeldt, Anders
Abstract: Background: In the maxillary incisor area infraposition of implant restorations can be an esthetic problem. Purpose: The aim was to analyze the prevalence of infraposition of single‐tooth implant restorations in the anterior maxilla in adolescent and adult patients. Material and Methods: The study comprised of 31 patients, 18 women and 13 men, with 39 restorations and with a mean and median age of 23.8 and 18.8 years, range 17.8 to 52.8 years, at the time of implant crown connection. The mean and median time in function for the restorations was 4.5 and 4.3 years respectively with a range of 3.3 to 6.6 years. Results: Twenty restorations 51%, showed no signs of infraposition. A slight infraposition (<0.5 mm) was seen in 36% of the restorations. Only in one patient, the observed infraposition of the implant crown was more than 1 mm. We found no significant difference of the observed level of vertical infraposition, Score A (0 mm) and Score B (<0.5 mm), in subjects where the restoration was placed before the age of 20 years compared to the older patients. There were no significant differences in changes of the vertical infraposition when comparing different parameters such as age, gender, jaw relation (Angle‐classes I‐III), overbite/overjet, occlusal contact on the implant crown, bone augmentation before or at implant installation or if orthodontic treatment of the neighboring teeth had been made before or after the implant installation. Conclusions: In the present study, there was a significant yet low correlation between the observed vertical infraposition of the single‐tooth implant restoration and the subject's evaluation of the esthetics of the restoration (VAS). Fifty‐one percent of the implant‐supported crowns, showed no signs of vertical infraposition. A slight infraposition (< 0.5 mm) was however seen in 36% of the restorations. Only one crown showed a vertical infraposition of more than 1 mm.